Analgesic and Antiinflammatory Activities of the Aqueous Extract from Plectranthus amboinicus (Lour.) Spreng. Both In Vitro and In Vivo. (21st July 2011) - Chiu, Yung-Jia; Huang, Tai-Hung; Chiu, Chuan-Sung; Lu, Tsung-Chun; Chen, Ya-Wen; Peng, Wen-Huang; Chen, Chiu-Yuan
Abstract : Plectranthus amboinicus (Lour.) Spreng. is a native Labiatae plant of Taiwan. The plants are commonly used in Chinese folk medicine for the treatment of cough, fever, sore throats, mumps, and mosquito bite. The aim of this study was to investigate the analgesic and antiinflammatory properties of the aqueous extract from Plectranthus amboinicus (PA) in vivo and in vitro . PA inhibited pain induced by acetic acid and formalin, and inflammation induced by carrageenan. The anti-inflammatory effect of PA was related to modulating antioxidant enzymes' activities in the liver and decreasing the Malondialdehyde (MDA) level and the production of tumor necrosis factor alpha (TNF- α ), and cyclooxygenase2 (COX-2) in edema-paw tissue in mice. In vitro studies show that PA inhibited the proinflammatory mediators in RAW 264.7 cells stimulated with lipopolysaccharide (LPS). PA blocked the degradation of I κ B- α and nuclear translocation of NF- κ B p65 subunit. Finally, the amount of carvacrol in the aqueous extract of PA was 1.88 mg/g extract. Our findings suggest that PA has analgesic and anti-inflammatory activities. These effects were mediated by inhibiting the proinflammatory mediators through blocking NF- κ B activation. Meanwhile, the effects observed in this study provide evidence for folkloric uses of Plectranthus amboinicus (Lour.) Spreng. in relieving pain and inflammation.